2006
DOI: 10.1002/mame.200600097
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Mechanical Properties of Vinylester Resin Matrix Composites Filled with Fly Ash

Abstract: Summary: Vinylester resin matrix composites were prepared with a fly ash loading of 30, 40, 50 and 60 wt.‐%. Flexural properties of the composites were investigated. It was found that the flexural strength was lowered in all the filled composites, but the flexural modulus showed a significant increase of 10, 57, 112% in case of 30, 40 and 50 wt.‐% fly‐ash‐loaded composites respectively, compared to the neat resin. However, there was a decrease in the mechanical properties in case of 60 wt.‐% fly‐ash‐filled com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…They suggested some possible mechanical anchorage between the filler and polymer matrix although there may not be much physical interaction between them. 47 The notched izod impact strength of the RHDPE/CF/MA-g-HDPE composites did not show any appreciable change with the incorporation of FACS (Table II) The mechanical findings were in agreement with the morphological interpretations from SEM as discussed in later section. The modulus increased significantly (p < 0.05) by 10,13,29, and 7% at 2.5, 5.0, 7.5, and 10 wt % FACS loading, respectively, in comparison to that without FACS.…”
Section: Effect Of Compatibilizersupporting
confidence: 82%
“…They suggested some possible mechanical anchorage between the filler and polymer matrix although there may not be much physical interaction between them. 47 The notched izod impact strength of the RHDPE/CF/MA-g-HDPE composites did not show any appreciable change with the incorporation of FACS (Table II) The mechanical findings were in agreement with the morphological interpretations from SEM as discussed in later section. The modulus increased significantly (p < 0.05) by 10,13,29, and 7% at 2.5, 5.0, 7.5, and 10 wt % FACS loading, respectively, in comparison to that without FACS.…”
Section: Effect Of Compatibilizersupporting
confidence: 82%
“…The fracture toughness of the 15 w/t% sawdust (300-425 μm) reinforced vinyl ester composite was 34.83 MPa Figure 13, magnified at 200 times, illustrates the fractured surface of neat vinyl ester resin, illustrating faint striations followed by a turbulent flow pattern of the fractured zone. The fractured surface is relatively smooth, typical of brittle materials, and it is similar to the fractured surface of neat vinyl ester by other studies [18,19]. Figure 14 shows the fractured surface of 5% w/t sawdust (300-425 μm) reinforced vinyl ester composite, 200X.…”
Section: Cost Analysissupporting
confidence: 74%
“…They also blamed voids for the lowering in flexural strength. 18 Bose et al also reported a lowering in tensile strength values of Nylon 6/fly ash composites with the increase in fly ash loading and in case of flexural strength, they observed an initial rise up to 20 wt % filler content, followed by a reduction in values. The latter was similar to that of this study.…”
Section: Materials and Methodologymentioning
confidence: 91%